2023
DOI: 10.1111/1756-185x.14986
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine in the treatment of patients with hyperuricemia: A randomized placebo‐controlled double‐blinded clinical trial

Pui‐Ying Leong,
Huang‐Hsi Chen,
Shuo‐Yan Gau
et al.

Abstract: BackgroundStudies have demonstrated the association of hyperuricemia with hypertension, metabolic syndrome, cardiovascular disease, and chronic renal disease. Although Western medicine presents promising effects for treating hyperuricemia and gout, identifying a safe and effective alternative to traditional Chinese medicine (TCM) for treating hyperuricemia is essential.ObjectiveTo evaluate the efficacy and safety of TCM formulas, “Wu‐Ling San” and “Yin Chen Wu‐Ling San,” in patients with hyperuricemia.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…26,27 The effect of Traditional Chinese Medicine on rheumatic diseases has been long discussed. 28 The current study found that ADA combined with TwHF was effective in treating RA patients who did not respond well to MTX and that there were no significant differences in efficacy and safety in the treatment of ADA combined with TwHF and ADA combined with MTX. Previous studies have shown that TwHF monotherapy for RA is not less effective than MTX monotherapy and that the combination of TwHF and MTX is more effective than MTX alone.…”
Section: Discussionmentioning
confidence: 55%
“…26,27 The effect of Traditional Chinese Medicine on rheumatic diseases has been long discussed. 28 The current study found that ADA combined with TwHF was effective in treating RA patients who did not respond well to MTX and that there were no significant differences in efficacy and safety in the treatment of ADA combined with TwHF and ADA combined with MTX. Previous studies have shown that TwHF monotherapy for RA is not less effective than MTX monotherapy and that the combination of TwHF and MTX is more effective than MTX alone.…”
Section: Discussionmentioning
confidence: 55%
“…47 In addition, the role of herbs in lowering uric acid should not be overlooked. 48,49 Lifestyle adjustments involve reducing the intake of purine-rich foods and increasing water consumption. 50 Future research should explore safer and more personalized treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of medication, drugs like allopurinol and febuxostat reduce uric acid production by inhibiting xanthine oxidase 47 . In addition, the role of herbs in lowering uric acid should not be overlooked 48,49 . Lifestyle adjustments involve reducing the intake of purine‐rich foods and increasing water consumption 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) and edible plants have emerged as alternative treatments for HU [38]. Long-term clinical practice with TCM formulas has shown relative safety for short-term HU treatment [39]. TCM and natural products offer similar UA-lowering efficacy as Western medicine but with fewer adverse effects [40].…”
Section: Treatment Strategiesmentioning
confidence: 99%